2016
DOI: 10.17556/jef.68600
|View full text |Cite
|
Sign up to set email alerts
|

Lise Matematik Öğretmenlerinin Türevin Tanımına ve Türev-Süreklilik İlişkisine Yönelik Pedagojik Alan Bilgileri

Abstract: ÖzetBu araştırmanın amacı lise matematik öğretmenlerinin türevin tanımına, türevin tanımının görselleştirilmesine ve türev-süreklilik ilişkisine yönelik pedagojik alan bilgilerini konu alanı bilgisi bağlamında incelemektir. Öğretmenlerin konu alanı bilgileri; türevi tanımlama ve örneklendirme, türevin tanımını görselleştirme ve türev-süreklilik arasındaki ilişkiyi açıklama şeklinde üç başlık altında incelenmiştir. Nitel araştırma modellerinden özel durum çalışmasına göre desenlenen bu araştırma 2015-2016 öğret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
3
0
5
Order By: Relevance
“…Teachers have similar difficulties as students regarding the concept of derivative. However, compared to the number of studies conducted with secondary or undergraduate level students, there are relatively few studies focusing on describing or supporting mathematics teachers' knowledge of derivative and rate of change (e.g., Akkoç et al, 2008;Kertil, 2014, Byerley & Thompson, 2017Duran & Kaplan, 2016;Gökçek & Açıkyıldız, 2016;Rodríguez-Nieto et al, 2021;Yoon et al, 2015). Akkoç et al (2008) investigated the developments in one prospective teachers' content knowledge during a technology-enriched workshop and they reported an enrichment in her conception of a derivative as an instantaneous rate of change in a real-life context.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Teachers have similar difficulties as students regarding the concept of derivative. However, compared to the number of studies conducted with secondary or undergraduate level students, there are relatively few studies focusing on describing or supporting mathematics teachers' knowledge of derivative and rate of change (e.g., Akkoç et al, 2008;Kertil, 2014, Byerley & Thompson, 2017Duran & Kaplan, 2016;Gökçek & Açıkyıldız, 2016;Rodríguez-Nieto et al, 2021;Yoon et al, 2015). Akkoç et al (2008) investigated the developments in one prospective teachers' content knowledge during a technology-enriched workshop and they reported an enrichment in her conception of a derivative as an instantaneous rate of change in a real-life context.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Öğrencilerin çoğu tanımı, tanımdaki sezgisel anlama olan "farkların oranının limiti", "fonksiyondaki değişimin değişkendeki değişime oranının limiti" ve "bir fonksiyonun bağlı olduğu bir değişkendeki çok küçük değişim ile bu değişime bağlı olarak fonksiyondaki küçük değişimin birbirine oranlanması" fikirleri doğrultusunda yorumlamamıştır. Çalışmadan elde edilen bu sonuç analiz öğrencilerinin türevin tanımını bilmedikleri (Desfitri 2008'den Akt: Desfitri, 2016Duru, 2006), tanımı anlayamadıkları (Akkaya, 2009;Bingölbali, 2013;Duran, 2018;Habre & Abbloud, 2006) ve tanımın içeriklerini özümseyemedikleri (Açıkyıldız, 2013;Doruk, 2016;Duran, 2018;Duran & Kaplan, 2016) yönündeki çalışma sonuçlarını desteklemiştir. Orton (1983) bu çalışmada olduğu gibi, öğrencilerin türevi sezgisel olarak anlamakta güçlük yaşadıklarını belirtmiştir.…”
Section: Tartişma Ve Sonuçunclassified
“…In these studies, it was determined that the students were not able to understand the concept 'the limit of the difference quotient', the intuitive meaning underlying the formal definition of derivative in relation to algebraic representation (Hähkiöniemi, 2005retrieved from Bingölbali, 2013. It was also found that the students did not understand the definition of the derivative (Akkaya, 2009;Bingölbali, 2013;Duran, 2018;Habre & Abbloud, 2006;Zandieh, 1997) and did not explicitly addressed the relationship between derivative function and a point derivative in most cases (Park, 2011), and did not know the definition (Desfitri, 2008retrieved from Desfitri, 2016Duru, 2006), and also could not fully internalize the contents of the definitions (Açıkyıldız, 2013;Doruk, 2016;Duran, 2018;Duran & Kaplan, 2016). This shown that students did not fully internalize the roles of definitions in terms of mathematical knowledge (Viholainen, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The examination of these studies indicated that the majority of the studies were in the field of student coaching and especially in the field of science (Alaca, 2014;Çakır, 2013;Erkoç, 2019;Etyemez Demirboğa, 2014;Gürel, 2017;Kalçık, 2018;Şimşek, 2016;Yalçıntaş, 2019;Yilgen, 2014). Document analysis studies often concentrate on foreign language teaching, Turkish education history, mathematics teaching, science teaching, and more on teaching programs, comparison of theses or research articles (Çavdar, 2019;Duran, 2018;Görler, 2017;Güngör, 2016;Karasolak, 2017;Özer, 2018;Yiğit, 2014;Yücel Ertem, 2018;Yüksel, 2019). This study can be said to have an original nature because it is the first study at the national level due to its topic and method.…”
Section: Discussionmentioning
confidence: 99%